POSSIBILITY Of EXPROPRIATION Of GERMAN PRIVATE PROPERTIES AS WAR REPARATIONS AFTER THE 2ND WORLD WAR - Sobański, Piotr (In Gremium. Studies in History, Culture and Politics, 2017)
The point of the deliberations of the paper is an analysis of expropriation of German private properties after the 2nd World War. The reparations after the 2nd World War were influenced by the regulations of the Treaty of Versailles, which was the peace settlement, signed in 1919. The right to war reparations was the legal title of measures against German properties. The reparations are payments intended to cover damage or injury inflicted as a result of war. The measures of particular countries against German assets were taken in accordance with public international law.